Uji Stabilitas Fisik dan Kimia Sediaan Tablet Paracetamol terhadap Suhu dan Kelembaban Selama Penyimpanan - Muhammad Hafiz Adha; Jaida Rahma; Nor Latifah (Jurnal Sains Farmasi Dan Kesehatan, 2025)
This study aims to evaluate the physical and chemical stability of paracetamol tablets under varying temperature and humidity conditions, specifically room temperature (25°C ± 2°C) and high temperature (40°C ± 2°C) with relative humidity of 75% ± 5%. The stability test was conducted over a period of three months with observations at 30-day intervals. Parameters assessed included changes in color, tablet hardness, active ingredient content (measured using UV-Vis spectrophotometry), and pH of the dissolved solution. The results showed that tablets stored at high temperature experienced a decrease in paracetamol content by up to 5.8% and visible color changes starting from the second month. These findings highlight the importance of proper storage conditions to maintain the quality, safety, and efficacy of pharmaceutical products.